Overcoming being Overwhelmed in the Trump Era - Gill, Navyug (Radical Teacher, 2017)
This piece offers a teaching strategy to help students overcome the sense of being overwhelmed by the 2016 election and its immediate aftermath. I emphasize the importance of understanding Trump in a broader historical context yet with a sharper analytical focus. By attending to the specificity of language, separating policy from rhetoric, and recognizing the limitations of the current political spectrum, students learn to avoid the pitfalls of caricature and exceptionality. Ultimately this empowers them to imagine and engage in a wider, more creative and transformative world of politics.